2009
DOI: 10.1177/1460408609346207
|View full text |Cite
|
Sign up to set email alerts
|

Acute scaphoid fracture: a review

Abstract: The scaphoid is by far the most commonly fractured carpal bone. Occult fractures, imperceptible on initial radiographs and a reputation for non-union make diagnosis and management challenging. The past few years have seen significant advances in the assessment and surgical treatment of scaphoid fractures. This article reviews the published literature relating to acute scaphoid fractures and examines the advances that have been made in management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 69 publications
(74 reference statements)
2
5
0
Order By: Relevance
“…According to published literature, most scaphoid fractures occur in young adult men, between 20 to 30 years of age and in women, between the ages of 40-50 years [9]. We observed similar patterns in our study.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…According to published literature, most scaphoid fractures occur in young adult men, between 20 to 30 years of age and in women, between the ages of 40-50 years [9]. We observed similar patterns in our study.…”
Section: Discussionsupporting
confidence: 92%
“…The proportions of fractures occurring on the left and right sides were also determined to investigate whether there was a difference between males and females. It has been reported that scaphoid fractures occur more frequently in younger men, who may fracture more commonly on the right side from manual labour activities [9]. Females may be expected to fracture more evenly on both sides, as they have been reported to sustain scaphoid fractures at an older age, mainly as a result on falling onto an outstretched hand.…”
Section: Descriptive Statisticsmentioning
confidence: 98%
See 3 more Smart Citations